CORRELATION BETWEEN MICROSTRUCTURAL AND CORROSION RESISTANCE OF BORON-MODIFIED DUPLEX STAINLESS STEEL PROCESSED BY SPRAY-FORMING - Pariona, Moises Meza (International Journal of Research -GRANTHAALAYAH, 2021)
In this work was investigated the duplex stainless steel modified by boron by spray-forming, in order to characterize the using different techniques, optical microscopy, SEM-FEG, X-ray diffraction, Rama spectroscopy and hardness (VH) and Thermo-Calc software, with goal of determining the corrosion resistance. The corrosion resistance test was performed in aerated solution of 0.1 M, immersed in different aggressive media electrolytes, alkaline and acidic mediums. As result through the EDS technique was verified that in the phase the Cr element predominates, but in the phase the Fe and Ni elements prevail. XRD spectra shown different meta-stable phases and mainly the (FeCr)2B phase, the percentage of the and phases are similar. Besides, the measurement was around 460 HV. Furthermore, impedance plots at different electrolytes had linear behavior, which their polarization resistances are extremely high in all solutions. However, the potential of corrosion whose magnitude is small, also the rates were close to zero. Consequently, the corrosion resistance in all studied solutions were extremely high and it can be attributed due to presence of the (FeCr)2B phase, meta-stables phases and similar proportion of the three phases present. This alloy can be successfully used in the chemical, oil and gas industries and petrochemical process plants.